Hematological and serum biochemistry parameters as a prognostic indicator of severally ill versus mild Covid-19 patients: A study from tertiary hospital in North India - Deval B. Dubey; Sridhar Mishra; Himanshu D. Reddy; Aliya Rizvi; Wahid Ali (Elsevier, 2021)
Background/objectives: In, India coronavirus disease (COVID-19) cases are on the rise in terms of the total number of cases. Findings on clinical and hematological parameters alone carry no significance apart from telling patients present status and hence are diminutive. This study aims to assess the hematological and serum biochemistry parameters and correlate them with the presenting symptoms and severity of disease which can help predict the need for intensive care unit (ICU) care, help in triage, assess the severity of the disease which will help clinicians decide their future course of action and further improve patients clinical outcome. Methods: A total of 200 COVID-19 positive patients were included. Hematological and serum biochemistry parameters were recorded for the patients at the time of admission and categorized as mild, moderate, and severely ill based on clinical status and then admitted into various wards. Results: Total leucocyte count (TLC) was significantly different and higher in severely ill patients (13,200 ± 6,999.2) compared to cases presented with mild and moderate symptoms (12,100 ± 6,488.41& 8,788.20 ± 4,954.32, p = 0.001). The mean difference of TLC, Neutrophil% (N%), Lymphocyte% (L%) and Monocyte (M%) was significantly different between mild and moderate symptoms cases (p = 0.030, p = 0.002, p = 0.004 & p = 0.003). Between groups comparison of moderate vs. severely ill cases showed a significant difference in TLC (p = 0.000), N% (p = 0.000), L% (0.000), and L/N ratio (p = 0.002). The serum ionic calcium (Ca), random blood sugar (RBS), C-reactive protein (CRP), fibrinogen, prothrombin (PT), International Normalized Ratio (INR), ferritin, and Lactate Dehydrogenase (LDH) level also differed significantly between mild, moderate and severely ill cases (p = 0.001, p=<0.001, p = 0.002, p=<00.1, p = 0006, p = 0.005, p=<0.001 and p=<0.001) respectively. Comparison of the mild vs. severely ill cases showed a significant difference in urea, fibrinogen, and procalcitonin (PCT) level (p = 0.005, p = 0.000 & p = 0.048) respectively. Conclusion: The preliminary findings of this study suggest hematological and serum biochemistry parameters could be used as a screening tool to identify patients requiring intensive care and thus allowing clinical stratification and triage at the time of presentation.